2021
DOI: 10.1016/j.seizure.2021.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Modeling seizures: From single neurons to networks

Abstract: Dynamical systems tools offer a complementary approach to detailed biophysical seizure modeling, with high potential for clinical applications. This review describes the theoretical framework, allowing theorizing certain properties of seizures and their classifications according to their dynamics properties at onset and offset. We describe various modeling approaches spanning different scales, from single neurons to large-scale networks. We try to offer a large accessible overview through nonexhaustive example… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…Such microelectrode recordings showed that neuronal activity during seizures does not necessarily correspond to synchronized spikes over the whole neuron population, as previously modeled ( Soltesz and Staley, 2008 ), including models at different scales from cellular to whole-brain levels ( Depannemaecker et al, 2021 , 2022 ). In fact, it turns out that the dynamics of neural networks during seizures are more complex ( Jiruska et al, 2013 ) and still poorly understood.…”
Section: Introductionsupporting
confidence: 60%
“…Such microelectrode recordings showed that neuronal activity during seizures does not necessarily correspond to synchronized spikes over the whole neuron population, as previously modeled ( Soltesz and Staley, 2008 ), including models at different scales from cellular to whole-brain levels ( Depannemaecker et al, 2021 , 2022 ). In fact, it turns out that the dynamics of neural networks during seizures are more complex ( Jiruska et al, 2013 ) and still poorly understood.…”
Section: Introductionsupporting
confidence: 60%
“…Since seizures can be triggered in most brain regions from most species, it has been proposed that simple mathematical rules should be sufficient to describe such a basic form of physiological activity, particularly their dynamics. Several conceptual frameworks have been proposed to explain seizure dynamics (Depannemaecker et al, 2021;Naze, 2015;Naze et al, 2015;Soltesz & Staley, 2008;Staley, 2015;Stefanescu et al, 2012;Y. Wang et al, 2017;Wendling et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This multi-omic study allows authors to revisit the data accumulated in recent years and points to the involvement of a wide variety of mechanisms and signaling pathways that underlie the pathophysiology of MTLE-HS. Depannemaecker and collaborators [24], present various modeling approaches spanning different scales, from single neurons to large-scale networks providing a basis for theorizing certain properties of seizures and for their classification according to their dynamical properties at onset and offset.…”
Section: Celebrating the Lasse 15th Editionmentioning
confidence: 99%